# Answer to Question #20812 in Trigonometry for Kristen Woods

Question #20812

if f(x)=x^2+3 and g(x)=3x-1

then find the following

1a. (f+g)(x)

1b. (f+g)(3)

1c. (f-g)(x)

then find the following

1a. (f+g)(x)

1b. (f+g)(3)

1c. (f-g)(x)

Expert's answer

1a

(f+g)(x)=f(x)+g(x)=x^2+3+3x-1=x^2+3x+2

1.b

(f+g)(x)=x^2+3x+2

(f+g)(3)=3^2+3*3+2=9+9+2=20

1c.

(f-g)(x)= x^2+3-(3x-1)=x^2-3x+4

(f+g)(x)=f(x)+g(x)=x^2+3+3x-1=x^2+3x+2

1.b

(f+g)(x)=x^2+3x+2

(f+g)(3)=3^2+3*3+2=9+9+2=20

1c.

(f-g)(x)= x^2+3-(3x-1)=x^2-3x+4

## Comments

## Leave a comment